Value, conflict, and order Berlin, Hampshire, Williams, and the realist revival in political theory - Hall, Edward (Political scientist) (The University of Chicago Press, 2020)
"Is the purpose of political philosophy to draw a picture of an ideal society and show what that implies for the way we should behave toward one another? Or is political philosophy more useful if it takes the world as it is, a world in which people disagree about morality, and thinks about how people, who disagree about fundamental values, can live together. This approach, a sort of political realism as Edward Hall characterizes it, is prominent in the work of Bernard Williams, Stuart Hampshire, and Isaiah Berlin. Hall builds on the work of these thinkers to establish a political realist's theory of politics for the 21st century"--Publisher's description.